PENENTUAN HARGA POKOK BERAS DI KECAMATAN KOTAMOBAGU TIMUR KOTA KOTAMOBAGU - Juliana R. Mandei; Theodora Katiandagho; Charles R. Ngangi; Jilly N. Iskandar (Sam Ratulangi University, 2011)
The research with the title